Preparation and radiation shielding features of high density, transparent borosilicate glasses with different Bi2O3 contents - M.I. Sayyed; M. Rashad; Chaitali V. More; Anjan Kumar (Nuclear Engineering and Technology, 2024)
This work assessed highly effective bismuth borosilicate glasses' nuclear radiation shielding capabilities in terms of different concentrations of Bi2O3. Melt-quenching was the method used to create the glasses. The Phy-X/PSD program was used to compute the μm values. The bismuth borosilicate glasses' nuclear radiation shielding properties were determined in the 0.015–15 MeV energy range. Increasing Bi₂O₃ concentration resulted in an increase in mass attenuation coefficient, linear attenuation coefficient, and effective atomic number. Conversely, the half value layer and mean free path values decreased. The B48Bi17 sample, with its largest Zeff, is a great gamma attenuator. The results of a new study may help to clarify the nature of the Bi2O3 additive used in borosilicate glasses, which are a potential form of shield for use in industrial and medical radiation facilities.